Efficacy and Safety of Manual Partial Red Cell Exchange in the Management of Severe Complications of Sickle Cell Disease in a Developing Country - B. F. Faye; D. Sow; M. Seck; N. Dieng; S. A. Toure; M. Gadji; A. B. Senghor; Y. B. Gueye; D. Sy; A. Sall; T. N. Dieye; A. O. Toure; et al. (Advances in Hematology)
Introduction. The realization of red cell exchange (RCE) in Africa faces the lack of blood, transfusion safety, and equipment. We evaluated its efficacy and safety in severe complications of sickle cell disease. Patients and Method. Manual partial RCE was performed among sickle cell patients who had severe complications. Efficacy was evaluated by clinical evolution, blood count, and electrophoresis of hemoglobin. Safety was evaluated on adverse effects, infections, and alloimmunization. Results. We performed 166 partial RCE among 44 patients including 41 homozygous (SS) and 2 heterozygous composites SC and 1 S/β0-thalassemia. The mean age was 27.9 years. The sex ratio was 1.58. The regression of symptoms was complete in 100% of persistent vasoocclusive crisis and acute chest syndrome, 56.7% of intermittent priapism, and 30% of stroke. It was partial in 100% of leg ulcers and null in acute priapism. The mean variations of hemoglobin and hematocrit rate after one procedure were, respectively, +1.4 g/dL and +4.4%. That of hemoglobin S after 2 consecutive RCE was −60%. Neither alloimmunization nor viral seroconversion was observed. Conclusion. This work shows the feasibility of manual partial RCE in a low-resource setting and its efficacy and safety during complications of SCD outside of acute priapism.